Pengaruh Financial Distress dan Growth Opportunity terhadap Konservatisme Akuntansi - Febry Valentina; Dirvi Surya Abbas; Wati Yaramah (BADAN PENERBIT STIEPARI PRESS, 2024)
The purpose of this study is to determine the Effect of financial distress and growth opportunity on accounting conservatism in state-owned companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 research period. The population of this research includes all state-owned companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 period. The sampling technique uses purposive sampling technique. Based on predetermined research criteria, 13 companies were obtained. The type of data used is secondary data obtained from the Indonesian Stock Exchange (BEI) website. The analytical method used is panel data regression analysis. The research results show that financial distress has an effect on accounting conservatism, but growth opportunity has no effect on accounting conservatism